Common octopus settled in human-altered Mediterranean coastal waters: from individual home range to population dynamics. (2nd March 2018) - Arechavala-Lopez, P; Minguito-Frutos, M; Follana-Berná, G; Palmer, M
Abstract: A spatially explicit capture-recapture (SCR) model was applied to estimate simultaneously population parameters and individual activity (i.e. home range size) of O. vulgaris, based on experimental mark-recapture data in a human-altered Mediterranean coastal area. Seventy-two octopuses were captured, tagged with subcutaneous PIT-tags and released. Nineteen tagged individuals were recaptured (recapture rate: 26.4%) in the same area over the study period, which spanned over 6 months. Population sizes and densities decreased over the study period, from 337 octopuses (8 ind. ha −1 ) in September-October to 105 octopuses (2.5 ind. ha −1 ) in February-March. The highest recruitment probability was estimated to occur at the beginning of the study but it clearly decreased over time, while mortality probability during a fishing period slightly increased. Mean specific growth rate was 0.82 ± 0.11 day −1 . Individual home range or activity area ranged from 2.8 ha to 7.3 ha (median home range radius: 121.8 m). Overall, these results suggest that human-altered coastal habitats, which are characterized by abundant shelters, abundant food and absence of predators, can act as settlement and growth areas for juveniles and adults of O. vulgaris . Furthermore, the methodologies applied in this study are recommended as innovative tools to improve management actions of coastal resources.